2004
DOI: 10.1161/01.str.0000143451.14228.ff
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Receptor Blockade Attenuates Glucose Hypermetabolism in Perihematomal Brain After Experimental Intracerebral Hemorrhage in Rat

Abstract: Background and Purpose-Intracerebral hemorrhage has no effective treatment. The delayed appearance of edema, apoptosis, and inflammation in perihematomal brain suggests that these events may be targets for therapeutic intervention. To develop successful treatments, we must learn more about the effects of hemorrhage on brain tissue. In this study, we investigated the acute metabolic effects of intrastriatal hemorrhage in rat brain. Methods-Lysed blood or saline (50 L each) was injected into the striatum of male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 28 publications
2
39
1
Order By: Relevance
“…This protection is roughly equivalent to that produced by MK801. The findings are consistent with our previous report that the Src kinase inhibitor PP1 improves outcomes following whole blood injections, and the protection was similar to that afforded by MK801 (Ardizzone et al, 2004, Ardizzone et al, 2007.…”
Section: Discussionsupporting
confidence: 92%
“…This protection is roughly equivalent to that produced by MK801. The findings are consistent with our previous report that the Src kinase inhibitor PP1 improves outcomes following whole blood injections, and the protection was similar to that afforded by MK801 (Ardizzone et al, 2004, Ardizzone et al, 2007.…”
Section: Discussionsupporting
confidence: 92%
“…23,24 Blockade of posttraumatic and post-ICH hyperglycolysis in animal models by glutamate receptor antagonists is consistent with glutamate-mediated hyperglycolysis. 25,26 However, the time course of the increase in glutamate after ICH (peaking within hours) does not correspond well to the transient increase in FDG uptake we observed.…”
Section: Discussioncontrasting
confidence: 64%
“…47 Our previous study showed increased cerebral glucose utilization at 3 hours and 8 hours after ICH. 30 Blocking NMDA or AMPA glutamate receptors blocked increased glucose metabolism. 30 These data coupled with studies showing that pp60-Src (Src) potentiates the function of NMDA receptors through direct phosphorylation of the NR2A subunit, 13 anchoring NMDA receptors 48 and phosphorylation of the scaffolding protein PSD95 at the postsynaptic density of NMDA receptors, 49 suggest that blocking Src might block NMDA receptor activation and, in turn, block the ICHinduced increases of glucose metabolism in this study.…”
Section: Discussionmentioning
confidence: 99%
“…30 Blocking NMDA or AMPA glutamate receptors blocked increased glucose metabolism. 30 These data coupled with studies showing that pp60-Src (Src) potentiates the function of NMDA receptors through direct phosphorylation of the NR2A subunit, 13 anchoring NMDA receptors 48 and phosphorylation of the scaffolding protein PSD95 at the postsynaptic density of NMDA receptors, 49 suggest that blocking Src might block NMDA receptor activation and, in turn, block the ICHinduced increases of glucose metabolism in this study. 30 Alternatively, because Src phosphorylates many targets, Src might modulate glucose metabolism after ICH by phosphorylating other molecules, perhaps even on non-neuronal cells.…”
Section: Discussionmentioning
confidence: 99%